2020
DOI: 10.1080/09669582.2020.1839758
|View full text |Cite
|
Sign up to set email alerts
|

Tourists’ water conservation behavior in hotels: the role of gender

Abstract: Hotels and destination managers are increasingly expressing concern about the impacts of climate change and sustainable water use, especially in crowded and water-scarce destinations. The aim of this study is to examine gender differences in hotel guests' reported water conservation behavior (WCB) when on vacation. The study examines several factors that can potentially affect these gender differences, namely attitudes toward water conservation, normative and hedonic motives, destination problem awareness, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 106 publications
(143 reference statements)
0
10
0
Order By: Relevance
“…Consequently, the effects of HTI on residents' support for tourism is under-researched (Fan et al, 2017b;Eusébio et al, 2018). In addition, a large body of research suggests that many factors, such as personality traits (Kim et al, 2021), gender (Casado-Díaz et al, 2020) and green marketing (Liao et al, 2020), motivation (Kim et al, 2017) moderate the links between attitudes and intention. However, research examining the cultural boundaries of the utility of attitudes on intention is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the effects of HTI on residents' support for tourism is under-researched (Fan et al, 2017b;Eusébio et al, 2018). In addition, a large body of research suggests that many factors, such as personality traits (Kim et al, 2021), gender (Casado-Díaz et al, 2020) and green marketing (Liao et al, 2020), motivation (Kim et al, 2017) moderate the links between attitudes and intention. However, research examining the cultural boundaries of the utility of attitudes on intention is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…In the study of Shin et al (2020), gender difference was not found between consumers' AT and their purchasing intention or consumers' SNs and their purchasing intention. However, some different findings have been found in some previous studies (Casado-Dı ´az et al, 2020;Moon, 2021). Moon (2021) found that gender significantly moderated the relationship between consumers' SNs and their intention to visit a green restaurant.…”
Section: Discussionmentioning
confidence: 80%
“…Moon (2021) found that gender significantly moderated the relationship between consumers’ SNs and their intention to visit a green restaurant. Casado-Díaz et al (2020) identified that the association between guests’ attitudes towards in-room water-conservation and reported behaviour was greater for women than that for men. The different findings might be explained by the different attributes of behaviour itself.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations